Isolation of chemical constituents from methanol extract in stem bark of pithecellobium jiringa / Nosafarina Abdul Manaf - Abdul Manaf, Nosafarina (Faculty of Applied Sciences, 2016)
This study is designed to isolate and identify chemical constituents from the methanol extract in stem barks of Pithecellobium jiringa. The chemical constituents from methanol extract were isolated and purified by using liquid liquid extraction, silica gel in column chromatography and were analyse by using GC-MS and FT-IR techniques. The structures of the chemical constituents were identified on the basis of spectral data on GC-MS, and FT-IR. n-Hexadecanoic acid, Hexadecanoic acid (ethyl ester), 1,2,4-Trioxolane-2 octanoic acid, 5-octyl (methyl ester), Eicosane and two of Hexadecanoic acid (methyl ester) constituents at different peaks were isolated from methanol extracts of stem barks of Pithecellobium jiringa. The results suggested that the current studies on Pithecellobium jiringa is still far from being well known and therefore more studies need to be done for better understanding of this plant.